The beautiful face of war: refreshing epic and reworking Homer in Flavian poetry - Lovatt, Helen (De Gruyter, 2017)
At Statius Thebaid 8.342-427 the second day of fighting begins, after Amphiaraus is swallowed up by the earth. Although this is far from being the beginning of the poem, not even the beginning of the fighting, Statius in this passage creates an image of new war, by going back to the beginnings of epic (evoking Homer in various ways). He characterises war as not just glorious but even beautiful: pulcher adhuc belli uultus ('the face of war is still beautiful'). This paper focuses on three main areas: first, how does Statius refresh the idea of epic by going back to Homer? How does this help Flavian epic to continue despite being in the shadow of Virgil? Secondly, how does Statius' approach to the topos of the march out compare to the approaches of Valerius and Silius? Can we distinguish different approaches to the renewal of epic amongst the three Flavian epicists? Thirdly, how does the image of fresh, new, beautiful war compare with images of war in other genres, focusing on the Flavian period? I will contextualise Flavian epic, first by looking at Martial and Tacitus, then by branching out more widely to explore the topos of the march out to battle. The paper aims to enrich our appreciation of the ways in which ancient writers approached the idea of war as beautiful.